A parametric study of the elastic stress distribution in a pin-loaded tube with multiple pinning. (15th November 2015) - Grant, R.J.; Thienpont, E.; Allard, L.J.
Highlights: A parametric study of the stress distribution in a pin-loaded tube was made. The work considers multiple pinning in a variety of configurations. Through thickness effects exist from out-of-plane deformations and unequal loading. Constructing a joint employing 3 pins has advantages over a 2 pin arrangement. The peak hoop stress can be reduced by 42% compared with using only a single pin. Abstract: This paper describes a numerical study of the stress distribution in a pin-loaded tube, loaded in tension, where more than one pin is used. The effect of changing the inter-pin distances, pin diameters and pin orientation (i.e. in-line or crossed) have been analysed and discussed. The study shows that there are significant through thickness effects as a result of out-of-plane deformations coupled with an unequal load distribution between each of the pins. Various configurations of pin positions are compared, and it is demonstrated that the joint design can be optimised by crossing, changing the diameter or moving particular pins. It is shown that constructing a joint employing three pins has advantages over a two pin arrangement and that the peak circumferential stress around a pin hole can be reduced by approximately 42% compared with using only a single pin: especially significant when fatigue loadings are considered.